Contributions of mindfulness in high-risk pregnancy: a mixed methods systematic review - Dutra, Irina Neves (2025)
Introduction Experiencing a high-risk pregnancy entails pathological situations with repercussions that can interfere with maternal-fetal well-being and increase maternal anxiety. Mindfulness emerges as one of the techniques used to improve the quality of care in the transition period resulting from pregnancy, which, through meditative practice, seeks to understand observation and the nature of the lived experience, resulting in a progressive state of clarity and awareness. Objective This review assessed the contributions of applying mindfulness in high-risk pregnancies. The review considered experimental, quasi-experimental studies, randomized controlled trials and non-randomized controlled trials. Observational studies were also considered. Evidence published in the last 5 years was considered. Methods This systematic review was conducted in accordance with the Joanna Briggs Institute methodology for systematic reviews of mixed methods using a convergent integrated approach to synthesis and integration. We searched for published and unpublished English, Portuguese and Spanish-language studies and grey literature. CINAHL Ultimate, MEDLINE (via Pubmed), Web of Science, Academic Search Complete, EBSCO Host Open Dissertations and Open Access Theses and Dissertations were searched in April–May 2024. Two authors screened titles and abstracts before full-text screening and data extraction. Two authors reviewed the extracted data. Results Ten articles were included in the review: 5 randomized controlled trials, 3 quasi-experimental studies and 2 mixed-methods studies. 9 studies measured the effectiveness of the application of mindfulness-based interventions on high-risk pregnant women and 1 assessed the acceptance of mindfulness intervention. Six studies measured the effects of the application of mindfulness in high-risk pregnant women in depressive symptoms, two reported the outcomes in stress, five on anxiety, two on psychological well-being, one on gestational weight gain, one in prenatal attachment and another in sleep quality. Conclusions Long term reduction of depressive symptoms, anxiety and stress and increased psychological well-being are contributions of mindfulness on high-risk pregnant women. The existing evidence on other contributions of the application of mindfulness is limited, further research being necessary.